Histopathological Analysis of the Product of Conception following First Trimester Spontaneous Abortion in Bharatpur Hospital - Sapkota, Ram Prasad Sapkota; Pokhrel, Sunilmani; Pariyar, Sanjib (Journal of Bharatpur Hospital, 2025)
Background Spontaneous abortion is one of the most common problems encountered in women of reproductive age group leading to retained product of conception in most of the cases. The aim of this study is to evaluate the histopathological findings of the product of conception in first trimester spontaneous abortion. Methods A hospital based descriptive cross-sectional study was conducted at the Gynecology department of Bharatpur Hospital, Chitwan, Nepal from August 15, 2024 to May 15, 2025. This study was conducted among the women admitted with diagnosis of first trimester spontaneous abortion. Ethical approval was taken from IRC of Bharatpur hospital. Data was entered and analyzed using SPSS 16 using descriptive statistical tools. Results Among 121 cases of spontaneous abortions, the majority (57.5%) of patients belonged to age group 21-30 years. On admission, the majority (43.8%) of patients were diagnosed with incomplete abortion. Histopathological examination confirmed the product of conception in 73.5% patients, partial mole in 9.1% patients, complete mole in 0.8% patients, decidual reaction in 10% patients and hydropic changes in 6.5% patients. Conclusions The histopathological examination of the product of conception proved to be an important tool in conforming normal products of conception and to find out possible pathologies like molar pregnancy and hydropic changes that necessitate special follow up and further management.